Species A Rotavirus (RVA) Isolated from Sewage in Nigeria, 2014: Close Genetic Relatedness of Partial G, P, and NSP4 Gene Sequences Encoding G1 with Cogent Genes of Other Asian and African Rotaviruses. (24th June 2018) - Motayo, Babatunde Olanrewaju; Adeniji, Johnson Adekunle; Faneye, Adedayo Omotayo
Abstract : Rotavirus has been identified as a major cause of gastroenteritis in Nigeria. There is limited information on the intragenotype diversity of Nigerian rotavirus isolates. We therefore investigated the molecular characteristics of some rotavirus gene sequences detected in sewage from Nigeria. Seven sewage samples, out of a total of 68, tested positive for rotavirus RNA (10.3%). Genotype G1P[ 4 ] was the most common genotype (5 isolates) and one isolate for genotypes G1P[8] and G3P[6]. Phylogenetic analysis of the partial VP7 gene of 3 G1P[ 4 ] isolates analyzed identified them as genotype G1 Lineage 2 along with Chinese strains with 99.1% to 100% amino acid similarity. Amino acid substitutions D-97→E and S-147→D/N were observed within the 7-1a and 7-2 domains of VP7 gene among the study G1P4 isolates in reference to vaccine strain RotaTeq®. Phylogenetic analysis of the G3P[ 6 ] study isolate identified it as genotype G3 Lineage 3, forming a monophyletic cluster with 100% bootstrap value with other West African strains G3 isolates. Phylogenetic analysis of GIP[ 4 ] VP4 genes identified them as P4 Lineage 5, while 3 NSP4 gene sequences belonged to genotype E1, while 1 belonged to E2. The results from this study represent phylogenetic analysis of partial gene sequences of environmental group A rotavirus (RVA) isolates from Nigeria.